Flannery O'connor's women as victims and survivors of a patriarchal society - Pereira, Elizabeth Anne (2015)
This in-depth study of the selected works by Flannery O’Connor aims to address the scarcity of feminist research on her literary works. This research incorporates textual analysis and close reading of eight selected short stories. This study is based on the feminist concept of patriarchy and women’s empowerment, thus striving to magnify the positive traits of female characters while contrasting common negative perceptions of O’Connor’s women characters. Besides that, this study attempts to illustrate the struggles of the women characters due to their gender as females in 1940’s and 1950’s southern patriarchal American society. Since O’Connor’s female characters have been always viewed through prejudicial lens by past scholars, this study focuses on rebranding these female characters by giving them a more positive appeal. This study acknowledges the barrage of negative perceptions by past scholars who label O’Connor’s female characters as naïve, physically unattractive, handicapped,unintelligent, self-righteous, pessimistic, superficial and not strong willed. Conversely this study was able to rebrand the tarnished image of the female characters by highlighting their positive traits such as optimism, independence, motherly love, steely resilience, strong faith in God, saintly patience and bold streaks of womanly courage. Besides that, this study was able to illustrate the struggles these women face such as sexual harassment, domestic violence, misogyny, sexism and verbal abuse. Furthermore, a future study through the lens of psychoanalysis is recommended that would delve into the psyche of O’Connor’s female characters and unearth the effects of male oppression on them.